Modelling success factors influencing industrialized building system project performance using dematel - Yusmin, Jaffar (2021)
Industrialized Building System (IBS) is the term to represent the prefabrication concept in the Malaysian construction industry that uses standardized building components mass produced in a factory or on the site. Adoption of IBS in Malaysia in still very low whereby only 10% of total awarded projects are of IBS project. On average, only 61% of total IBS is considered as highly performing IBS projects with IBS Score of more than 80. Performance of IBS can be measure in the form of IBS Score where government made it compulsory for IBS projects to achieve a minimum score of 70 to be considered as a performing IBS project. This study is directed towards identifying factors that exact influence towards project performance and examine the relationship of the factors to create models to serve as alternative in decision making process towards higher performance of IBS project. Through literature review, a total of 6 main factors and 17 subfactors were derived and served as the theoretical framework for this study. Respondents for this study were consisted of experts in IBS with minimum 16 years of experience coming from G7 contractors. This study integrated DEMATEL method of analysis to capture causal-effect relationship and prominence value to generate impact relation map as basis for the proposed models. Analysis done on the factors showed that knowledge and expertise of IBS as the most important factors followed by management, training, financial, integration, while IBS policies resulted as the least important factor among all 6 factors. Impact relation map from DEMATEL showed that IBS policies is the most influential factor. The proposed models provide intel on which factor to be given top priority and which factor can provide the biggest improvement towards the performance of IBS project when given the proper consideration. Both models proposed presents the ideal sequence of factor engagement and traces the influence-based relationship of factors that can be used as guide to improve performance of IBS particularly towards achieving higher IBS Score as well as to increase transition of contractors into IBS method of construction.